Parents’ perceptive regarding the effect of internet use on students with and without learning difficulties - Mohammad Abed Sakarneh; Ayed Hanna Ziadat; Zahraa Jameel Rahahleh (International Journal of Evaluation and Research in Education (IJERE), 2022)
In the recent digital era, the use of the internet worldwide has become vital in almost all fields of life, and no one can deny its significant impact on activities of different age groups. The current study investigated the effect of internet usage on students with/without learning difficulties in Jordanian primary schools from point of view of their parents. For this purpose, a questionnaire consisting of 21 items was built by the researchers including these areas: social interactions, communication, health, entertainment, learning, academic activities, behavior, and security. The targeted population was the parents of students with/without learning difficulties in public and private schools. The findings indicated that parents perceive a moderate level of effect of internet usage on their children’s most activities except entertainment and security which have a high impact. Moreover, parents of students with learning difficulties perceive a positive impact of the internet in enhancing their children’s learning abilities.